PENGARUH KOMPETENSI AUDITOR INTERNAL DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS AUDIT INTERNAL - Gunawi Tantra; Cris Kuntadi (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the impact of internal auditor competence and information technology utilization on internal audit quality. Auditor competence, including technical, analytical, and communication skills, along with the use of information technology such as audit software and data analytics, plays a significant role in improving internal audit quality. The findings show that these two factors complement each other, where auditor competence ensures effective use of technology, while technology enhances audit efficiency and accuracy. The results of this study provide insights into the importance of investing in auditor training and technology integration to improve audit quality that is faster, better, and more relevant.